Upaya Meningkatkan Deteksi Dini Kanker Payudara di SMKN 1 Cijulang Kabupaten Pangandaran - Muhammad Hasan Bashari; Hermin Aminah Usman; Dika Widia Nur Azizah; Defi Ardia Pramesti; Arima Kurnia Sari Dewi Nurcahyani; Atika Hana Ilyasa; Nadifah Diana Zalia; Risqi Dwi Putra; Lala Yuliani; Dwi Andini; Naura Mardhiyah; Putri Halleyana; Titing Nurhayati; Astrid Feinisa Khairani; Dimas Erlangga Luftimas; Rani Septriana (Jurnal Pengabdian Pada Masyarakat, 2018)
EFFORTS TO IMPROVE EARLY DETECTION OF BREAST CANCER IN CIJULANG 1 VOCATIONAL HIGH SCHOOL, PANGANDARAN REGENCY. The high mortality rate of breast cancer (BC) patients in Indonesia is associated with conditions of most patients come to doctor in an advanced stage of BC. This is due to the low BC awareness of Indonesian women. This community service program (PPM) is intended to increase knowledge of adolescent women about early detection of BC. This action was conducted by BC awareness workshop to 114 female students of Vocational High School (SMK) 1 Cijulang, Pangandaran district, West Java. The profile of participants showed that 64% of participants are 17 years old and mostly from Cijulang and Cimerak sub-districts. In addition, the majority of participants were not aware of BC, indicated by lack of knowledge of BC signs and symptoms (97%), and low confident of doing breast self-examination (BSE) (30%). Moreover, there were 7% of the participants were smoking which is known to be one of the major risk factors for BC. These findings point out conducting a program for increasing BC awareness among students. The program was managed by mini-lecture that focuses on BC risk factors, BC early detection and BSE (SADARI) using videos and simulation on a mannequin. This program was expected to have an impact on their families, indirectly. Ultimately, this will increase the finding of new cases of BC which will increase their life expectancy.